2022
DOI: 10.1101/2022.08.24.22279150
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Post-COVID syndrome prevalence and risk factors in children and adolescents: A population-based serological study

Abstract: Objectives Post-COVID syndrome remain poorly studied in children and adolescents. In this study, we aimed to investigate the prevalence and risk factors of pediatric post-COVID in a population-based sample, stratifying by serological status. Study design We used data from the SEROCoV-KIDS cohort study (State of Geneva, Switzerland), which included children (aged 6 months to 17 years) selected from random samples drawn from state registries or who had a household member participating in a COVID-19 seroprevalenc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 29 publications
(44 reference statements)
0
2
0
Order By: Relevance
“…Although the prevalence of symptoms decreased with time, 33% of patients still had symptoms at 12 months: 16% reported fatigue, 10% had a loss of taste or smell, 9% had persistent dyspnea, 10% had headaches, 9% had sleep disorders, 7% had difficulty concentrating, and 7% had myalgia. In young children and adolescents, studies have shown the persistence of symptoms beyond 3 months and potentially with long-term effects, especially in adolescents [ 6 , 8 ]. To date, there is little information about the long-term evolution and treatment options for post–COVID-19, and symptoms may persist for years in a percentage of patients, with a potential impact on daily life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the prevalence of symptoms decreased with time, 33% of patients still had symptoms at 12 months: 16% reported fatigue, 10% had a loss of taste or smell, 9% had persistent dyspnea, 10% had headaches, 9% had sleep disorders, 7% had difficulty concentrating, and 7% had myalgia. In young children and adolescents, studies have shown the persistence of symptoms beyond 3 months and potentially with long-term effects, especially in adolescents [ 6 , 8 ]. To date, there is little information about the long-term evolution and treatment options for post–COVID-19, and symptoms may persist for years in a percentage of patients, with a potential impact on daily life.…”
Section: Introductionmentioning
confidence: 99%
“…Post-COVID-19 is prevalent in 10%-30% of outpatient adult individuals [2,3] and can potentially transform into a chronic condition, with patients suffering from symptoms over months to years. Additionally, new studies have shown that children can suffer from post-COVID-19 as well [4][5][6][7][8], even though the prevalence is overall lower in the pediatric population and can vary between 2% and 9%. In Geneva, Switzerland, the CoviCare follow-up program is a longitudinal outpatient cohort established in March 2020 [9], following the long-term evolution of symptoms after SARS-CoV-2 infection and their impact on daily life.…”
Section: Introductionmentioning
confidence: 99%